1994
DOI: 10.1172/jci117089
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A inhibits CD40 ligand expression in T lymphocytes.

Abstract: The ligand for CD40 is expressed on activated T lymphocytes and delivers contact-dependent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
90
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 51 publications
7
90
1
3
Order By: Relevance
“…15 X-linked hyper IgM (X-HIM) is a primary immune deficiency disease that results from defects in the gene for CD40 ligand. 16 CD40 ligand is a 39 kDa glycoprotein expressed transiently on the surface of activated CD4 + T cells 17 and delivers contact-dependent help to B cells and monocytes. 18 Affected patients suffer from recurrent infections including opportunistic infections, recurrent episodes of neutropenia and autoimmune disease, and have an increased likelihood of developing cancer.…”
Section: Introductionmentioning
confidence: 99%
“…15 X-linked hyper IgM (X-HIM) is a primary immune deficiency disease that results from defects in the gene for CD40 ligand. 16 CD40 ligand is a 39 kDa glycoprotein expressed transiently on the surface of activated CD4 + T cells 17 and delivers contact-dependent help to B cells and monocytes. 18 Affected patients suffer from recurrent infections including opportunistic infections, recurrent episodes of neutropenia and autoimmune disease, and have an increased likelihood of developing cancer.…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have previously showed that peripheral blood mononuclear cells (PBMCs) isolated from OLT recipients on conventional immunosuppression (tacrolimus, prednisolone) have impaired CD154 gene and protein expression after in vitro stimulation (12,28,29). This is thought to be the result of CD154 expression being partially dependant on the dephosphorylation of nuclear factor of activated T cells (NF-AT), the target of calcineurin antagonists, as the CD154 promoter has been found to contain an NF-AT binding site (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be the result of CD154 expression being partially dependant on the dephosphorylation of nuclear factor of activated T cells (NF-AT), the target of calcineurin antagonists, as the CD154 promoter has been found to contain an NF-AT binding site (28)(29)(30)(31). However, an increased intragraft expression of costimulatory transcripts in patients on calcineurin-based immunosuppression has been reported by some investigators (7).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclosporine (CsA), a powerful inhibitor of the calcineurin pathway, has been previously shown to eliminate CD40L expression on normal T cells. More specifically, only 4% of T cells from healthy subjects express CD40L upon activation, in the presence of CsA at concentrations of 100 ng/ml, compared to 62% in the absence of CsA (18).…”
Section: Regulation Of Cd40l Expressionmentioning
confidence: 99%